2009
DOI: 10.1007/s11121-009-0156-7
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Evaluation of the All Stars Prevention Curriculum in a Community After School Setting

Abstract: This study tested the effectiveness of a prevention curriculum, All Stars, as implemented in a year-long school-based after school program and provides an independent replication of the effects of All Stars on targeted mediators and problem behaviors using an experimental methodology. Middle school students (N = 447) who registered for the after school program were randomly assigned to the experimental or control condition. The sample included approximately equal proportions of males and females, was 70% Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…In the randomised All Stars trial, Gottfredson et al 92 found no statistically significant differences between All Stars and a control group offered minimal recreational activities on any past month substance use or on initiation of any of smoking, drinking, marijuana, inhalant or other (unspecified) illicit drug. The included sample consisted of 416 students completing the post-test survey near the end of the school year.…”
Section: Effects Of Interventions On Substance Usementioning
confidence: 99%
See 2 more Smart Citations
“…In the randomised All Stars trial, Gottfredson et al 92 found no statistically significant differences between All Stars and a control group offered minimal recreational activities on any past month substance use or on initiation of any of smoking, drinking, marijuana, inhalant or other (unspecified) illicit drug. The included sample consisted of 416 students completing the post-test survey near the end of the school year.…”
Section: Effects Of Interventions On Substance Usementioning
confidence: 99%
“…[90][91][92] This was delivered over the course of one academic year to students in Baltimore public schools using staff from a government agency charged with management and delivery of local parks and recreation programmes. Staff were trained in the delivery of general ASP activities as well as in the All Stars 90 appeared to be primarily oriented towards teaching participants skills and normative beliefs for the avoidance of substance use, some components promoted positive assets by encouraging participants to develop links with community groups, which was consistent with the programme's goals and aimed to improve students' communication with their families.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main reasons for valuing after-school programs is the need for after-school care and supervision of the children and adolescents of working parents (Gottfredson, Cross, Wilson, & Rorie, 2010) considering that young people are at higher risk of engaging in negative and unhealthy behaviors while their parents are at work (Gullotta, 2015). Another reason is related to the lack of time and adequate training by the teachers to include interventions in the school curricula geared towards pupils' personal and social development (Humphrey, Lendrum, & Wigelsworth, 2013;Perikkou, Kokkinou, Panagiotakos, & Yannakoulia, 2015).…”
mentioning
confidence: 99%
“…Therefore, after-school programs may be a valuable option in particular cultural contexts where it is more unlikely to have SEL programs included in the academic curricula, as the same time as a safe and caring environment is offered to the children and adolescents while their parents are at work. However, after-school programs, since they are optional, have some particular limitations such as low attendance rates and possible sample losses (Gottfredson et al, 2010;Gopalan et al, 2013;Hayes, Chapple, & Ramirez, 2014). Therefore, after-school program activities need to be appealing to the target population in order to maximize their attendance and continuation.…”
mentioning
confidence: 99%